RISIKO USAHATANI TOMAT (LYCOPERSICUM ESCULENTUMMILL) DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (Risks of Tomato (Lycopersicum Esculentum) Farming in Lembah Gumanti District Solok Regency) - LEOVITA, ANGELIA; FAUZI, DIAN; SIREGAR, WILDA ASTRIANI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
This study aims to determine analyze the characteristics of tomato farmers, analyze the income of tomato farmers and analyze the risk level of tomato farming in Lembah Gumanti District, Solok Regency. The method used in this study is quantitative descriptive The analysis used is income, variety, standard deviation, coefficient of variation, and lower limit. The respondents who were sampled were 40 farmers with a population of 423 farmers and were selected randomly (proportional random sampling). The results showed that the characteristics of tomato farmers have a productive age of 25 to 48 years, a low level of education, farmers who already have long farming experience. The amount of cash costs incurred by farmers is IDR 6,456,733.33 / MT and the calculated costs are IDR. 4,919,309.63/MT with revenue of Rp 23,608,331.25/MT so that cash income is Rp 17,209,386.82/MT and total income is Rp 12,290,077.19/MT. Tomato farming has a production risk level with a KV value of 10.39, price risk with a KV value of 18.56, and income risk with a KV value of 13.36 with a lower income limit of Rp 10,450,763.47 where this figure will indicate the amount of loss that will be experienced by tomato farmer